PENGARUH KENYAMANAN DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK MELALUI FITUR AUGMENTED REALITY SHOPEE BEAUTYCAM DI MARKETPLACE SHOPEE - Mulyanie, Shintia Dewi; Syahputra, Syahputra (JURNAL ILMIAH EDUNOMIKA, 2024)
Along with the development of technology, the development of the cosmetic industry in Indonesia has increased rapidly. The increasing trend of online shopping makes cosmetics an item loved by society, especially women. However, the limitation of purchasing cosmetic products online is the limited experience of trying the products in person. Meanwhile, consumers want to save time and effort when making purchases. Shopee facilitates consumers by including augmented reality technology into its features Shopee beautycam, AR can increase convenience and support a practical lifestyle in purchasing products online. The adoption of AR encourages exploratory behavior in consumers, thus influencing them in making purchasing decisions. This study aims to discuss the influence of comfort and lifestyle factors and their relationship to purchasing decisions for cosmetic products. Data collection was carried out through the distribution of questionnaires using quantitative data analysis methods. Sampling using non-probability sampling method with a sample size of 200 respondents. The analysis method used is a multiple linear regression analysis test with the help of SPSS 27 software. Based on the results of multiple linear regression analysis, that simultaneously convenience and lifestyle have a significant effect on purchasing decisions.